Matrix Determinant 01

Algebra Level pending

\( Let\,\,f\left( x \right) =\left( p_1-x \right) \left( p_2-x \right) ...\left( p_n-x \right) \,\,and\,\,let \\ \varDelta _n=\,\,\left| \begin{matrix} p_1& a& a& a& ...& a& a\\ b& p_2& a& a& ...& a& a\\ b& b& p_3& a& ...& a& a\\ b& b& b& p_4& ...& a& a\\ \vdots& \vdots& \vdots& \vdots& & \vdots& \vdots\\ b& b& b& b& ...& p_{n-1}& a\\ b& b& b& b& ...& b& p_n\\ \end{matrix} \right| \\ If\,\,a\ne b\,\,then \\ \varDelta _n=\frac{Xf\left( a \right) -Yf\left( b \right)}{b-a} \\ What\,\,is\,\,X+Y\,\,? \\

\)

b - a 2a b + a 3b + 2a

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Sep 12, 2019

An elementary row operation (subtract the last but one row from the last) gives Δ n = p 1 a a a . . . a a b p 2 a a . . . a a b b p 3 a . . . a a b b b p 4 . . . a a b b b b . . . p n 1 a b b b b . . . b p n = p 1 a a a . . . a a b p 2 a a . . . a a b b p 3 a . . . a a b b b p 4 . . . a a b b b b . . . p n 1 a 0 0 0 0 . . . b p n 1 p n a \varDelta _n=\,\,\left| \begin{matrix} p_1& a& a& a& ...& a& a\\ b& p_2& a& a& ...& a& a\\ b& b& p_3& a& ...& a& a\\ b& b& b& p_4& ...& a& a\\ \vdots& \vdots& \vdots& \vdots& & \vdots& \vdots\\ b& b& b& b& ...& p_{n-1}& a\\ b& b& b& b& ...& b& p_n\\ \end{matrix} \right| \; = \; \left| \begin{matrix} p_1& a& a& a& ...& a& a\\ b& p_2& a& a& ...& a& a\\ b& b& p_3& a& ...& a& a\\ b& b& b& p_4& ...& a& a\\ \vdots& \vdots& \vdots& \vdots& & \vdots& \vdots\\ b& b& b& b& ...& p_{n-1}& a\\ 0& 0& 0& 0& ...& b-p_{n-1}& p_n-a\\ \end{matrix} \right| and hence Δ n = ( p n a ) Δ n 1 + ( p n 1 b ) p 1 a a a . . . a a b p 2 a a . . . a a b b p 3 a . . . a a b b b p 4 . . . a a b b b b . . . p n 2 a b b b b . . . b a \varDelta _n \; = \; (p_n-a)\varDelta_{n-1} + (p_{n-1}-b) \left| \begin{matrix} p_1& a& a& a& ...& a& a\\ b& p_2& a& a& ...& a& a\\ b& b& p_3& a& ...& a& a\\ b& b& b& p_4& ...& a& a\\ \vdots& \vdots& \vdots& \vdots& & \vdots& \vdots\\ b& b& b& b& ...& p_{n-2}& a\\ b& b& b& b& ...& b& a\\ \end{matrix} \right| where the last determinant is of an ( n 1 ) × ( n 1 ) (n-1)\times(n-1) matrix. Further row operations (subtracting the last row from all the others) give p 1 a a a . . . a a b p 2 a a . . . a a b b p 3 a . . . a a b b b p 4 . . . a a b b b b . . . p n 2 a b b b b . . . b a = p 1 b a b a b a b . . . a b 0 0 p 2 b a b a b . . . a b 0 0 0 p 3 b a b . . . a b 0 0 0 0 p 4 b . . . a b 0 0 0 0 0 . . . p n 2 b 0 b b b b . . . b a = a f n 2 ( b ) \left| \begin{matrix} p_1& a& a& a& ...& a& a\\ b& p_2& a& a& ...& a& a\\ b& b& p_3& a& ...& a& a\\ b& b& b& p_4& ...& a& a\\ \vdots& \vdots& \vdots& \vdots& & \vdots& \vdots\\ b& b& b& b& ...& p_{n-2}& a\\ b& b& b& b& ...& b& a\\ \end{matrix} \right| \; = \; \left| \begin{matrix} p_1-b& a-b& a-b& a-b& ...& a-b& 0\\ 0& p_2-b& a-b& a-b& ...& a-b& 0\\ 0& 0& p_3-b& a-b& ...& a-b& 0\\ 0& 0& 0& p_4-b& ...& a-b& 0\\ \vdots& \vdots& \vdots& \vdots& & \vdots& \vdots\\ 0& 0& 0& 0& ...& p_{n-2}-b& 0\\ b& b& b& b& ...& b& a\\ \end{matrix} \right| \; = \; af_{n-2}(b) so we have the recurrence relation Δ n = ( p n a ) Δ n 1 + a f n 1 ( b ) \varDelta_n \; = \; (p_n-a)\varDelta_{n-1} + af_{n-1}(b) It is now an easy induction to show that Δ n = b f n ( a ) a f n ( b ) b a \varDelta_n \; = \; \frac{bf_n(a) - af_n(b)}{b-a} for all n 1 n \ge 1 , making the answer a + b \boxed{a+b} .

Can you explain more detail the process from Δ n = ( p n a ) Δ n 1 + a f n 1 ( b ) \varDelta _n=\left( p_n-a \right) \varDelta _{n-1}+af_{n-1}\left( b \right) to Δ n = b f n ( a ) a f n ( b ) b a \varDelta _n=\frac{bf_n\left( a \right) -af_n\left( b \right)}{b-a} ? Thank you very much

Katyusha Le - 1 year, 9 months ago

Log in to reply

Δ 1 = p 1 = b f 1 ( a ) a f 1 ( b ) b a \varDelta_1=p_1 = \frac{bf_1(a)-af_1(b)}{b-a} , so the result holds for n = 1 n=1 . If Δ n 1 = b f n 1 ( a ) a f n 1 ( b ) b a \varDelta_{n-1}= \frac{bf_{n-1}(a)-af_{n-1}(b)}{b-a} then Δ n = ( p n a ) [ b f n 1 ( a ) a f n 1 ( b ) b a ] + a f n 1 ( b ) = b f n ( a ) a f n ( b ) b a \varDelta_n = (p_n-a)\left[\frac{bf_{n-1}(a)-af_{n-1}(b)}{b-a}\right] + af_{n-1}(b) = \frac{bf_n(a)-af_n(b)}{b-a} and so the result follows by induction.

Mark Hennings - 1 year, 9 months ago

Log in to reply

Thank you sir, finally I understand it now.

Katyusha Le - 1 year, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...